2010
DOI: 10.1007/s10551-010-0555-5
|View full text |Cite
|
Sign up to set email alerts
|

Management Students’ Attitudes Toward Business Ethics: A Comparison Between France and Romania

Abstract: ABSTRACT. This study focuses on the differences in the perception of business ethics across two groups of management students from France and Romania (n = 220). Data was collected via the ATBEQ to measure preferences for three business philosophies: Machiavellianism, Social Darwinism, and Moral Objectivism. The results show that Romanian students present more favorable attitudes toward Machiavellianism than French students; whereas, French students valued Social Darwinism and Moral Objectivism more highly. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 46 publications
2
63
0
2
Order By: Relevance
“…While businesses around the world have drafted codes in an attempt to reduce unethical behaviours, the effectiveness of such codes will be determined, to a great degree, by whether employees buy into the codes. By understanding the perceptions of future business leaders across the globe (see Bageac et al, 2011), codes that reflect and take into account cultural factors can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…While businesses around the world have drafted codes in an attempt to reduce unethical behaviours, the effectiveness of such codes will be determined, to a great degree, by whether employees buy into the codes. By understanding the perceptions of future business leaders across the globe (see Bageac et al, 2011), codes that reflect and take into account cultural factors can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Those students were selected as a prospects future managers, based on findings of previous studies (such as Preble, Reichel 1988;Shields et al 2013;Bageac et al 2011;Claar et al 2012).…”
Section: Methodology and Samplementioning
confidence: 99%
“…They (Preble, Reichel 1988) found out that respondents from both countries place considerable importance on morals in business and that there are only few significant differences. Shields et al (2013) used the same Questionnaire (ATBEQ) with suggested five philosophical categories (see Bageac et al 2011) to examine differences between USA and Japanese students. Those categories are: Machiavellian, Social Darwinism, Ethical Relativism, Legalism and Moral Objectivism.…”
Section: Research Studies On Attitudes Towards Corporate Social Respomentioning
confidence: 99%
See 1 more Smart Citation
“…They constitute future highly trained and skilled professionals (Hoon and Lim, 2001) and moreover, some of them are the next generation of business leaders and decision-makers (Bageac et al, 2011). Students and graduates have already developed strong work values based on their personal values, experiences and perceptions of what is fundamentally right or wrong (Judge and Bretz Jr., 1992).…”
Section: Challenges For College Students and Graduatesmentioning
confidence: 99%